2016
DOI: 10.4236/jbise.2016.94018
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Preconditioning Improved Neuroprotective Effect of Bone Marrow-Mesenchymal Stem Cells Transplantation in Acute Glaucoma Models

Abstract: This study explored the novel strategy of hypoxic preconditioning of Bone Marrow Mesenchymal Stem Cells (BM-MSCs) before intra vitreal transplantation to improve neuroprotective effects of Retinal Ganglion Cells (RGCs) in Acute Glaucoma Models. The methods of this research were isolated mesenchymal stem cells from the bone marrow of adult wild-type Sprague-Dawley (SD) rats. BM-MSCs were cultured under normoxic or hypoxic (1% oxygen for 24 hours) conditions. Normoxic or hypoxic BM-MSCs were transplanted intravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Despite intensive medical treatment, increasing evidence has suggested that acute glaucoma continues progressing to blindness in quite a few patients [3] . Until recently, elevated IOP has been considered to be a major risk factor for the pathogenesis of RGC death in acute glaucoma [4] . Nevertheless, the detailed mechanisms by which elevated IOP ultimately led to RGC apoptosis were largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Despite intensive medical treatment, increasing evidence has suggested that acute glaucoma continues progressing to blindness in quite a few patients [3] . Until recently, elevated IOP has been considered to be a major risk factor for the pathogenesis of RGC death in acute glaucoma [4] . Nevertheless, the detailed mechanisms by which elevated IOP ultimately led to RGC apoptosis were largely unknown.…”
Section: Introductionmentioning
confidence: 99%